Learning of Locomotor Movement for Elementary School 24 Sawang - Sayuti (Marga: Journal Of Innovation and Creatifity, 2023)
The general aim of this research is to improve elementary school students in locomotor movements. Apart from that, this research was conducted to obtain in-depth information about the application of locomotor movement learning. The design of this research is Action Research. The subjects in this research were 20 students of Elementary School 24 Sawang. This research was conducted in two meetings of two cycles. The first cycle shows that through action students can motivate themselves. From this cycle the results are 50% complete/passed and 50% not. In the second cycle, as a reflection of the first cycle, it also shows that actions motivate students. The results of the second cycle were 90% complete/passed and 10% not. Based on the results of this research, it can be concluded that: (1) Learning and understanding about locomotor movements improves student learning outcomes, (2) Learning locomotor movements motivates students and makes students active in participating in the learning process.